Stand Up Comedy to Develop Critical Analysis in the DEI Classroom - Caitlin Hawkins (Adult Education Research Conference, 2024)
This research explores how stand-up comedy from marginalized voices enriches diversity, equity, and inclusion (DEI) education, to foster critical analysis and emotional intelligence through self- and other awareness.
Keywords: Comedy; Adult Learning; Race; Diversity